2021
DOI: 10.1007/s42247-021-00276-5
|View full text |Cite
|
Sign up to set email alerts
|

Green composites in bone tissue engineering

Abstract: Natural and biodegradable polymers are of particular interest as green sources with low-cost and environmentally friendly features, and have been widely used for polymer composite development. The term "Green Composites" refers to polymer/ filler systems in which polymer, filler, or sometimes both components are green in view of sources from which they are yielded or their biodegradability. Natural fibers obtained from plants, animals, and/or geological processes are a big class of green sources widely applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 151 publications
0
13
0
Order By: Relevance
“…These implanted scaffolds are translational therapeutic approaches [5] using tissue engineering techniques [6] to treat degenerative diseases [7] and improve cartilage regeneration efficiency [8] for osteoarthritis patients. At present, titanium filler [9] is still the most commonly used in metallic scaffolds [10] in advanced combinations with polymer-based biomaterials [11][12][13] during the green composite fabrication processes [14]. However, the existing titanium dioxide filler in these applications [15] was over-strengthened or too hard, resulting in a thin oxide surface layer not being discussed [16].…”
Section: Introductionmentioning
confidence: 99%
“…These implanted scaffolds are translational therapeutic approaches [5] using tissue engineering techniques [6] to treat degenerative diseases [7] and improve cartilage regeneration efficiency [8] for osteoarthritis patients. At present, titanium filler [9] is still the most commonly used in metallic scaffolds [10] in advanced combinations with polymer-based biomaterials [11][12][13] during the green composite fabrication processes [14]. However, the existing titanium dioxide filler in these applications [15] was over-strengthened or too hard, resulting in a thin oxide surface layer not being discussed [16].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, materials used to repair bone defects are metallic biomaterials [ 36 , 37 ], bioceramics [ 38 , 39 ], and natural and synthetic polymers [ 40 , 41 ]. Hydroxyapatite (HA; (Ca 10 (PO 4 ) 6 (OH) 2 )) has been used as filler in polymer composites to improve the biocompatibility, mechanical strength, and porosity of biomaterials due to its similarity in structure and composition to bone and enamel, or to create polyester nanografts that impart the biodegradability and bioresorbability of polymers with their osteoconductivity, osteoinductivity, and osteointegration properties [ 42 , 43 ].…”
Section: Orthopedic Applicationsmentioning
confidence: 99%
“…20,21 As another example, a group of scientists demonstrated the feasibility of affecting cell differentiation and bioactivity (cell labeling) without growth factor addition using scaffold stiffness optimization. 16,22 Moreover, they can be utilized as wound dressing and tissue reconstruction systems. For example, some keratin-based bionanocomposites are used as implantable biomaterials that can be absorbed to the surrounding tissue as a function of time, which brings about tissue stability.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophilicity of bionanocomposites is the golden key, making them a practical option for biomedical applications such as cell and tissue engineering. For instance, their noncorrosiveness, toughness, and renewability have made them a nice option for bone tissue engineering instead of ceramics and alloys. Studies have shown that green nanocomposites own great advantages in comparison with the traditional ones such as cell permeability, cell/drug/gene/nutrient or growth factor delivery, biocompatibility, and biodegradability , as well as supporting cell adhesion or growth as a scaffold. , As another example, a group of scientists demonstrated the feasibility of affecting cell differentiation and bioactivity (cell labeling) without growth factor addition using scaffold stiffness optimization. , Moreover, they can be utilized as wound dressing and tissue reconstruction systems. For example, some keratin-based bionanocomposites are used as implantable biomaterials that can be absorbed to the surrounding tissue as a function of time, which brings about tissue stability.…”
Section: Introductionmentioning
confidence: 99%